The Role Of Global Education In The 21 Century Slovak Schools - Bacova, Beatrix; Lelakova, Eva (Advances in Social Sciences Research Journal, 2016)
Globalization affects all areas of life, the life of teachers including. The teaching profession is usually understood as a mission. The role of a teacher is to develop knowledge, abilities and skills of pupils and students and thus influence their values and opinions. Teachers present basic attributes of human lives’ interconnections to their students. They teach them to take into account the interests and living conditions of all people – to think in a global way. The authors of the present paper try to explain how the globalization influences teachers in their process of education and knowledge transfer and answer the questions dealing with the principles effecting the global education of both students and their teachers. They also point out that the work of teachers is not only very demanding but also significantly influencing the quality of the knowledge level of every society. Key words: Globalization, teacher, global upbringing, lifelong education, 21 century.